Implementation of National Standards of Educational Facilities and Infrastructure - Fitriyah Elyani (Indonesian Journal of Education (INJOE), 2022)
The implementation of the administration of equipment and supplies is already a routine job and people are faced with less significant difficulties, but to improve the work the experts suggest some guidelines for the implementation of the administration, the principal as an administrator should not be too busy himself directly with the affairs of the administration of equipment and supplies. teaching equipment, carrying out proper recording so that it is easy to do, administration of teaching equipment and equipment must always be reviewed from a service perspective to help facilitate the implementation of teaching programs The above conditions will be met if the administrator includes all teachers in planning the selection, distribution and use and supervision of teaching equipment and supplies